Aloe vera reduces gut inflammation induced by soybean meal in Atlantic salmon (Salmo salar) - Fehrmann-Cartes, Karen; Vega, Matías; Vera, Frank; Enríquez, Ricardo; Feijóo, Carmen G.; Allende, Miguel L.; Hernández, Adrián J.; Romero, Alex (Frontiers in Animal Science, 2022)
Plant-based protein sources, such as soybean, are widely used in fish nutrition due to their market availability, wide distribution and acceptable nutritional quality. However, in some fish species, soybean meal-based diets cause gut inflammation, decreasing both nutrient absorption and growth rates. A suitable alternative to avoid these problems could be the application of additives with anti-inflammatory activity to the diet. In this study, an Aloe vera (Aloe barbadensis Miller, AV) extract was analyzed as a dietary additive to reduce the gut inflammation in Atlantic salmon (Salmo salar) fed with soybean meal (SBM) diet. Fish were distributed in four duplicated groups and fed 28 days with fish meal control diet (FM), AV inclusion diet (AV), FM diet supplemented with AV (FM+AV), SBM diet to induce enteritis and SBM+AV. The fish gut response to these treatments was analyzed in distal intestine by histopathological scores, tissue morphometric measurements and immune gene expression parameters. The score results in fish fed with SBM-based diet clearly showed enteritis, meanwhile fish fed with AV supplemented diet significantly reduced the intestinal SBM signs of damage. These findings were associated to reduction of goblet cells number, lamina propria thickness and sub-epithelial mucosa size, with a significant decrease on pro-inflammatory cytokine il-1β to basal levels, similar to those present in fish fed FM diets. In conclusion, the administration of AV in salmon diet showed a protective intestinal activity against the detrimental effects of SBM, opening the possibility to improve its use as a feed additive in aquafeeds.